CNBC creating wealth : - O'Connell, Brian (John Wiley & Son, 2001)
The rapidly growing influence of the individual investor and the stunning evolution of technology are two of the most remarkable developments in the history of the financial world. In CNBC Creating Wealth, we help you take advantage of these fundamental changes to Wall Street and take charge of your own investing.